ANALYZE THE INDEPENDENCE OF CLASS VI STUDENT LEARNING ON SCIENCE SUBJECT IN SD NEGERI 5 KEBUMEN - Rosyada, Sittah Amrina; Irawati, Erlina Hanita; Suryandari, Kartika Chrysti (Universitas Sebelas Maret, 2018)
Learning independence is needed for students so that the learning process does not dependon others.This is based on indicators of learning independence which include responsibility,able to solve problems, use learning resources, and confidence.Seeing the importance oflearning independence for students, independence must exist in all subjects including science.More indicators are achieved showing students have high science learning independence.The purpose of this study was to describe the learning independence of class VI student learning in science subjects in SD Negeri 5 Kebumen academic Years 2018/2019.This research is a qualitative descriptive study that uses data collection techniques in the form of observation, questionnaires, and interviews.Analysis of the data used quantitatively and qualitatively. After analyzing the data, the average percentage of indicators was 31%.The results of the analysis, it can be concluded that the independence of class VI student learning in science subjects in SD Negeri 5 Kebumen was categorized as not goodaccepted 30/09/2018approved 12/10/2018published 30/10/2018 Learning independence is needed for students so that the learning process does not dependon others.This is based on indicators of learning independence which include responsibility,able to solve problems, use learning resources, and confidence.Seeing the importance oflearning independence for students, independence must exist in all subjects including science.More indicators are achieved showing students have high science learning independence.The purpose of this study was to describe the learning independence of class VI student learning in science subjects in SD Negeri 5 Kebumen academic Years 2018/2019.This research is a qualitative descriptive study that uses data collection techniques in the form of observation, questionnaires, and interviews.Analysis of the data used quantitatively and qualitatively. After analyzing the data, the average percentage of indicators was 31%.The results of the analysis, it can be concluded that the independence of class VI student learning in science subjects in SD Negeri 5 Kebumen was categorized as not good.